Gegenwartsdiagnosen: Kulturelle Formen gesellschaftlicher Selbstproblematisierung in der Moderne - Etzemüller, Thomas; Buschmann, Nikolaus; Alkemeyer, Thomas (transcript, 2019)
Diagnoses of the presence are booming: Imminent wars about the climate, the collapse of energy supply or even the extinction of mankind are being predicted. How do current diagnoses come about and how do they become effective?